Urine Donor–Derived Cell-Free DNA Helps Discriminate BK Polyomavirus-Associated Nephropathy in Kidney Transplant Recipients With BK Polyomavirus Infection - Chen, Xu-Tao; Chen, Wen-Fang; Li, Jun; Deng, Rong-Hai; Huang, Yang; Yang, Shi-Cong; Chen, Pei-Song; Jiang, Ting-Ya; Liu, Hai-Tao; Wang, Chang-Xi; Chen, Li-Zhong; Qiu, Jiang; et al. (Frontiers in Immunology, 2020)
Background: Studies have shown that plasma donor-derived cell-free DNA (dd-cfDNA) can predict renal allograft antibody-mediated rejection. This study was performed to evaluate the value of urine dd-cfDNA concentration and dd-cfDNA fraction (%) for discriminating BK polyomavirus associated-nephropathy (BKPyVAN) in kidney transplant recipients with urinary BK polyomavirus (BKPyV) infection. Methods: In this retrospective single-center observational study, we enrolled kidney transplant recipients who were diagnosed with urine BKPyV infection between August 2018 and May 2019 at the First Affiliated Hospital of Sun Yat-sen University. Urine dd-cfDNA was measured by using a novel target region capture sequencing methodology. The pathological diagnosis of BKPyVAN was confirmed by anti-SV40-T immunohistochemical staining and classified using the American Society for Transplantation schema. Receiver operating characteristic curve analysis was used to investigate the relations of urine dd-cfDNA and dd-cfDNA% to intrarenal allograft BKPyV infection states. Results: Totally 93 patients were enrolled, including 40 cases of proved BKPyVAN, seven cases of probable BKPyVAN, 23 cases of possible BKPyVAN, and 23 cases of resolving BKPyVAN. Urine dd-cfDNA level in proved BKPyVAN (22.09 ± 21.27 ng/ml) was comparable to that in probable BKPyVAN (15.64 ± 6.73 ng/ml, P = 0.434), but was significantly higher than that in possible BKPyVAN (5.60 ± 3.53 ng/ml) and resolving BKPyVAN (5.30 ± 3.34 ng/ml) (both, P < 0.05). Urine dd-cfDNA% of proved BKPyVAN (0.71 ± 0.21) was lower than that of probable BKPyVAN (0.91 ± 0.04, P < 0.001), but was significantly higher than that of possible BKPyVAN (0.56 ± 0.30) and resolving BKPyVAN (0.46 ± 0.28) (both, P < 0.05). For distinguishing biopsy-proved BKPyVAN from biopsy-excluded BKPyVAN, the discrimination capacity of urine dd-cfDNA (AUC: 0.842, 95% CI: 0.735, 0.918) was superior to that of plasma BKPyV DNA load (AUC: 0.660, 95% CI: 0.537, 0.769) with 0.181 (95% CI: 0.043-0.319) difference between areas under ROC curves (P = 0.010). Conclusion: The elevated urine dd-cfDNA level may help discriminate BKPyVAN in kidney transplant recipients with BKPyV viruria.